2014
DOI: 10.1021/nn503721h
|View full text |Cite
|
Sign up to set email alerts
|

How Adsorbate Alignment Leads to Selective Reaction

Abstract: There has been much interest in the effect of adsorbate alignment in a surface reaction. Here we show its significance for an electron-induced reaction occurring along preferred axes of the asymmetric Cu(110) surface, characterized by directional copper rows. By scanning tunneling microscopy (STM), we found that the heterocyclic aromatic reagent, physisorbed meta-iodopyridine, lay with its carbon-iodine either along the rows of Cu(110), "A", or perpendicular, "P". Electron-induced dissociative attachment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…We speculate that these two bonding configurations are switchable between each other by changing the local chemical environment, e.g. local geometry [37], at the interface, so that the electric conductance is thus, most likely, tunable by the interfacial environment. Our investigation reveals how the interfacial geometry correlates with the interfacial bonding configuration and could drastically influence transport properties.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that these two bonding configurations are switchable between each other by changing the local chemical environment, e.g. local geometry [37], at the interface, so that the electric conductance is thus, most likely, tunable by the interfacial environment. Our investigation reveals how the interfacial geometry correlates with the interfacial bonding configuration and could drastically influence transport properties.…”
Section: Discussionmentioning
confidence: 99%
“…1 Predicting reaction efficiencies in the two-dimensional confinement on surfaces thus demands a thorough knowledge about the adsorption orientations of the participating molecules. 2,3 This should be particularly true for the emerging field of on-surface synthesis on metal surfaces, which investigates individually synthesised molecules by scanning tunneling microscopy. 4,5 The first 6,7 and still most prominently employed 8,9 path in on-surface synthesis uses Ullmann-like coupling, 10 a C-C-coupling from halogenated molecules on the coinage metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has recently been shown that the relative alignment of the substrate and adsorbate atoms can influence reaction pathways and products. 40 Thus, a number of design parameters can be utilized to engineer structures with specific properties.…”
Section: Introductionmentioning
confidence: 99%